The Mechanism of State Regulation of Regional Services Markets as an Imperative to Reduce Territorial Socio-Economic Disparities - Klavdiya G. Erdyneeva; Klavdiya K. Vasilyeva; Elena V. Krysova; Tatyana V. Nikonova; Larisa E. Fatikhova; Tatyana I. Klimenko; Natalia A. Zaitseva; Ludmila V. Marfina (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the development of regional services' markets, as components ensuring the balanced socio-economic development of territories in a Federal state. Balanced territorial development of a Federal state involves the creation of conditions that allow each region to have necessary and sufficient resources to ensure decent living conditions of citizens, complex development and increase of competitiveness of the regional economy. The development of regional services markets can be considered as the imperative to reduce territorial socio-economic differentiation to the level, due to objective differences of the regions and to ensure balance of their revenue base and expenditure commitments. The purpose of this paper is to develop a mechanism of state regulation of regional services markets, ensuring the reduction of territorial socio-economic differentiation. A leading approach is the institutional approach that considers state regulation of the regional markets of services in the Federal state as a system of state control measures oriented on the goal that contributes to maximizing of the value of the assets of the service sector in the process of socio-economic activities and aimed at ensuring of a balanced socio-economic development of regions. The service sector is one of the most dynamic and growing segments of regional markets, as well as one of the characteristics of effective socio-economic policy in the region. The growth of assets yield from the service sector while risk diversification, focused on the development of regional services markets, meeting the needs of the population for public goods and improving the life quality will ensure a sustainable development of the Federal state. The paper presents perspectives on the content of the economic mechanism; identifies the functions of regional services markets; reveals the essence of the mechanism of state regulation of regional services markets and the characteristics of its structural components (goals, objectives, principles, actors, objects, forms, methods, tools); establishes the regularities in the process of state regulation of regional services markets. The paper submissions can be useful for specialists of Federal and regional authorities, local governments, line ministries, scientists interested in issues of regional economy and management of services sphere.